A TEMÁTICA MIGRATÓRIA NA REVISÃO PERIÓDICA UNIVERSAL DOS EUA: OPORTUNIDADE POLÍTICA DIANTE DO HEGEMON - Hernandez, Matheus De Carvalho; Rosa, William Torres Laureano Da [UNESP] (CEDEC, 2019)
The Universal Periodic Review (UPR) of the UN Human Rights Council (HRC) represents an innovation in the monitoring of human rights in international level. Discussing with hypotheses about shaming, this article stands back from the division between allies and non-allies to verify, within the scope of UPR, the postulation of the interests of the countries of the so-called Northern Triangle and Mexico on the protection of immigrants in the US. From the analysis of the recommendations made to the US in the migratory field, we argue that the primary variable to determine the relational dynamics of the decision to make and follow recommendations is the stock of undocumented migrants from the recommending countries in the US. The article concludes that UPR represents more than a space to produce shaming, but a political opportunity for countries, including the less powerful ones, to publicly put their interests before the hegemonic power, which makes the recent US exit from HCR even more serious.

A Revisão Periódica Universal (RPU) do Conselho de Direitos Humanos (CDH) da ONU representa uma inovação no monitoramento de direitos humanos no plano internacional. Ao debater com hipóteses sobre shaming, este artigo se afasta da divisão entre aliados e não-aliados para verificar, no âmbito da RPU, a postulação dos interesses dos países do chamado Triângulo Norte e México sobre a proteção dos imigrantes nos EUA. A partir da análise das recomendações realizadas aos EUA no campo migratório, argumentamos que a variável principal a determinar a dinâmica relacional da decisão de fazer e acatar recomendações é o estoque de migrantes indocumentados originários dos países revisores em território estadunidense. Conclui-se que a RPU representa mais do que um espaço de produção de shaming, mas uma oportunidade política para que os países, inclusive os menos poderosos, coloquem publicamente seus interesses diante da potência hegemônica, o que torna ainda mais grave a recente saída dos EUA do CDH.
THE MIGRATORY THEME IN THE US UNIVERSAL PERIODIC REVIEW: POLITICAL OPPORTUNITY IN THE FACE OF THE HEGEMON
Keywords: Universal Periodic Review; US; Migration; Human Rights; UN; Revisão Periódica Universal; EUA; Migrações; Direitos Humanos; ONU